Studies on the Storage Behaviour of Frozen Fish Fingers from Croaker and Perches - Reddy, Lakshminatha; T.M.R., Setty; K.C., Dora (Fishery Technology, 2025)
The frozen storage behaviour of breaded and battered "fish fingers" prepared from Croaker (Sciaenid spp.) and perches (Nemipterus japonicus) was studied for 22 weeks at - 20Â°C The products were acceptable even at the end of the storage period. Fish fingers prepared from pink perch was better than those from croaker meat organoleptically. The TVBN, TBA and PV values increased during the storage period, but the values were within the acceptable limits.